An Anlysis 21st Century Skills in Cambridge Textbook Used Representation in A Cambridge Textbooks Used the In The Indonesia EFL settings - Khoerunisa, Khoerunisa (Journal of Applied Linguistics (ALTICS), 2025)
The study analyzed the extent to which 21st-century skills are integrated into Cambridge English textbooks “Think Second Edition 1 A2 student Book” for grade 8, with a focus on core subjects, learning and innovation skills, information, media, and technology skills, and life and career skills as outlined by the Partnership for 21st Century Skills (P21). The content analysis method categorized the 690 tasks into various components such as goal, input, procedure, teacher/student role, and setting based on Nunan (2004). The results showed that the teacher and learner role is a component that needs to be more minimally integrated. Meanwhile, the results from integrated 21st-century revealed that 3 out of 5 core subject skills (Global Awareness, Health Literacy, and Environmental Literacy) were incorporated into textbooks. All four skills in the learning and innovation categories (Critical Thinking, Communication, Collaboration, and Creativity) and all skills in the information, media, and technology categories are present. However, only two out of five skills (Flexibility and Adaptation and Social and Cross-Cultural Skills) are included in the life and career skills category. Although Cambridge English textbooks effectively incorporate many 21st-century skills, there are significant shortcomings, especially in financial literacy, civic literacy, and some life and career skills. Likewise, the topic of ICT could be more minimally accomplished. With that in mind, it is recommended that educators supplement textbooks with additional materials and activities that address these areas that need to be improved to provide more balanced skills.